(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2016)
Assessment on the level of pollution of Turag river water was performed by measuring various physico-chemical parameters. Water samples were collected five times in a year both dry and rainy season at five different locations: Bishwa Ijtema field, Tongi Bridge, Kachare ghate, River side of Dhaka Dying and Effluent of Dhaka Dying. Most of the measured parameters exceeded the permissible limit of standard level. Values for different parameters at different points were recorded such as Temperature (T): 23.9 to 31.2°C, pH: 7.2 to 10.1, Salinity: 64 to 933 ppm, Total dissolved solid (TDS): 90 to 1244 ppm, Electrical Conductivity (EC): 135 to 1856 µs/cm, Dissolve oxygen (DO): 0.5 to 3.6 mg/L and Chemical oxygen demand (COD): 220 to 1170 mg/L. The concentration (ppm) of heavy metals were also observed such as Chromium (Cr) 0.0339 to 0.6334, Cadmium (Cd) 0.0068 to 0.0170, Nickel (Ni) 0.1282 to 0.6207, Cooper (Cu) 0.0148 to 0.1703 and Zink (Zn) 0.0366 to 0.1890 at dry season. The values of different parameters determined are above the safe limits recommended by DoE, EQS and WHO. Therefore, it can be concluded that water relieved from selected locations were not suitable for human consumption during the period of experiments. Bangladesh J. Sci. Ind. Res. 51(3), 193-202, 2016